-4(2x-3)=14

Simple and best practice solution for -4(2x-3)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2x-3)=14 equation:



-4(2x-3)=14
We move all terms to the left:
-4(2x-3)-(14)=0
We multiply parentheses
-8x+12-14=0
We add all the numbers together, and all the variables
-8x-2=0
We move all terms containing x to the left, all other terms to the right
-8x=2
x=2/-8
x=-1/4

See similar equations:

| 35=5n+5 | | 3x+7-x=31+8x-5x+22 | | -3(x+)=39 | | Y=138-4x | | 2x-111=x+1 | | 2x-111=x=1 | | ̶12+4n=6(n̶2) | | 2x^2+6x=2x^2+15 | | 9+4g+5=7+2g+3 | | 7x^+2=20 | | 7x+1=-3+2 | | (2x+3)(8x+1)=(4x-5)(4+5)+2 | | 11/8=g-2/4 | | 7x+7=-3+2 | | 8(10-4)=2k | | 6x+3+4x=13 | | 12b=-7b | | 5(x-5=3x-43 | | (-7y)-8y=22 | | (2x-3)2=2x+3)2+48 | | 5(5-2)=4(10+5x) | | 3(10-2x)54=0 | | 2x-16=30-7x | | 2a+16=5a-19 | | (3n+15)+(2n+20)=180 | | 5x+1+3=-7 | | x2+17=x(x-11)-49 | | 17+3x+2=6x+3 | | 63=2x×31.5/x | | X(2x+1)=73 | | -18-6x=36 | | 10c+2=-18 |

Equations solver categories